Tourism Suitability Index of The Mangrove Area of Pulau Banyak Village, Langkat, North Sumatra: An Ecological Approach - Manullang, Helentina Mariance; Lubis, Zulkarnain; Sabrina, Raja (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2024)
This study aims to obtain data on the suitability of ecotourism areas based on ecological parameters. The parameters observed were mangrove density & thickness, tidal height, mangrove species diversity, and the types of biota that live in it. To calculate mangrove density, the quadratic transect method was used with a size of 10 x 10 m as many as 20 plot pieces. While mangrove thickness is calculated by measuring the outer distance of mangroves towards the mainland. Furthermore, the parameters of biota diversity were carried out by direct observation techniques at the research site. The results of the analysis showed a mangrove thickness of 197.37 metres with a density of 1,520 individuals/ha. There are 10 mangrove species including Sonneratia alba, Avicennia marina, Rhizophora apiculate, R. mucronate, Bruguiera gymnorrhiza, Lumnitzera littorea, Acanthus ilicifolius, Acrostichum speciosum, Pemphis acidula, Nypa fruticans. The average tide height is 1.24 m and 20 species of biota consisting of 3 bivalve species, 1 Gastropoda, 6 fish, 6 birds, 2 shrimps, and 2 crabs. The results of the tourism suitability analysis showed 91% with a very suitable category